Integrasi Batuk Efektif dan Aromaterapi Peppermint untuk Menurunkan Frekuensi Napas pada Pasien Pneumonia: Studi Kasus dari Indonesia. - Facsha Nabila, Sallma; Cahyati, Yanti; Rahman, Arip (Jurnal Kesehatan Mahardika, 2025)
Background: Pneumonia is a lower respiratory tract infection that affects the alveoli and is characterized by cough, shortness of breath, and increased respiratory rate. It remains a global health concern, with approximately 9.2 million cases reported annually worldwide and 309,838 cases in Indonesia in 2018. Non-pharmacological interventions such as effective coughing techniques and peppermint aromatherapy may help alleviate clinical symptoms, particularly by reducing respiratory rate. Objective: This study aimed to determine the effect of implementing effective coughing techniques and peppermint aromatherapy on changes in respiratory rate among pneumonia patients. Method: This qualitative study used a case study approach conducted over three weeks, from April 8 to April 28, 2025. The intervention was applied for three consecutive days to two respondents, with daily monitoring of respiratory rate changes. Results: After the intervention, the first respondent’s respiratory rate decreased from 25 breaths per minute to 19 breaths per minute, while the second respondent’s rate decreased from 27 breaths per minute to 20 breaths per minute. Conclusion: The combination of effective coughing techniques and peppermint aromatherapy effectively reduced respiratory rate in pneumonia patients. This intervention can be applied independently as a supportive therapy to help improve respiratory function in patients with pneumonia.